KEMAMPUAN MEMBACA PEMAHAMAN ISI RUPAMA SISWA KELAS VIII SMP NEGERI 1 MANGARABOMBANG KABUPATEN TAKALAR: READING COMPREHENSION ABILITY OF RUPAMA CONTENT OF GRADE VIII STUDENTS OF SMP NEGERI 1 MANGARABOMBANG TAKALAR DISTRICT - Nurhikma; Syamsudduha; Hajrah (Journal of Applied Linguistics and Literature, 2025)
The purpose of this study is to describe the reading comprehension ability of rupama content of class students. This research is a quantitative descriptive research. The population of this study included all VIII grade students of SMP Negeri 1 Mangarabombang Takalar Regency totalling 326 students. The sample determination in this study used Krejcie Morgan theory with a sample of 177 students. The technique used in data collection in this study was a multiple choice test totalling 25 numbers. The data obtained were analysed using quantitative descriptive analysis. The results showed that students who scored 86-100 were 5 people (3%) categorised as very capable, students who scored 75-85 were 20 people (11%) categorised as capable, students who scored 70-74 were 5 people (3%) categorised as less capable and students who scored 0-69 were 147 people (83%). Thus, it can be stated that the ability to read comprehension of Rupama content of students in class VIII of SMP Negeri 1 Mangarabombang Takalar Regency is categorised as unable